Membangun Aplikasi Administrasi Laundry Berbasis Android Menggunakan Model Prototype - Dwi Ananto, Wahyu; Primajaya, Aji; Yusup, Dadang (STKIP Subang, 2026)
Advances in information technology have encouraged businesses to improve service efficiency, including in the laundry industry, which requires a fast, accurate, and easy-to-use administration system. Bunda Laundry, as the location of this study, still relies on manual recording, which often leads to errors in recording and calculation, complicates the order tracking process, and creates obstacles in preparing accurate income reports. This research was conducted to design and develop an Android-based laundry administration application using the Software Development Life Cycle (SDLC) prototype model methodology. This approach was chosen because it supports a gradual development process that can be tailored to user needs. The application was built using the Kotlin programming language and Firebase as the database, and is equipped with two separate interfaces, namely the admin interface for data management and reporting, and the user interface for ordering services and monitoring work status. Testing was carried out through Black Box Testing to ensure that the functions ran according to requirements and User Acceptance Testing to assess the level of user acceptance. The results of the study show that all the main features of the application run according to user needs based on the results of Black Box Testing. The results of User Acceptance Testing also show that the application is well accepted and is considered capable of improving the regularity and efficiency of the laundry administration process. In addition, the application generates sales reports that can support business owners in monitoring business development. Thus, the application that was built successfully fulfilled the research objectives and provided an effective solution that can be directly applied in the management of laundry business administration.